Evaluation and Temporal-Spatial Deconstruction for High-Quality Development of Regional Marine Economy: A Case Study of China - An, Dong; Shen, Chunlei; Yang, Lin (Frontiers in Marine Science, 2022)
High-quality development of marine economy has become a realistic choice to stimulate the vitality of regional economic growth and achieve the goal of building a powerful nation in marine economy.This study constructs an evaluation index system from efficiency,coordination,innovation, sustainability, openness and shareability to analyze the high-quality development level and temporal-spatial heterogeneity of China’s regional marine economy from 2010 to 2018.Methods used in this paper are the entropy,kernel density estimation and partial spatial autocorrelation analysis.The results are shown as following:(1) The high-quality development level of China’s regional marine economy shows a slow fluctuating and upward trend,coordination,sustainability and innovation are the primary driving forces.The ranking of the three marine economic circles in development quality of marine economy is Eastern> Southern>Northern, the ranking of coastal provinces is Guangdong> Shanghai> Shandong> Zhejiang> Fujian> Tianjin> Jiangsu> Liaoning> Hainan> Hebei> Guangxi. The primary driving forces for Guangdong,Shanghai,Shandong and Zhejiang leading other coastal areas are openness,efficiency,innovation and sustainability respectively;(2) The temporal differentiation of China’s regional marine economy shows a dynamic evolution process of obvious in early stage, alleviating in middle stage and balance in later stage;(3) The spatial zoning types and high-quality development paths of 11 coastal provinces are determined based on spatial differentiation:Shanghai and Zhejiang are high-value congregate types and named as demonstration regions,which should build global marine center cities with deepening regional cooperation and high-standard opening-up;Shandong and Guangdong are high-value discrete types and named as key engine regions,which should enhance the international competitiveness of marine industry with scientific and technological innovation;Tianjin,Hebei and Liaoning are low-value congregate types and named as potential zooming regions,which should improve the efficiency of marine resources utilization with regional cooperation;Jiangsu,Fujian,Hainan and Guangxi are low-value discrete types and named as land-sea coordination regions,which should build modern and characteristic marine industrial system with coordinated land and sea.